PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN VARIABEL MEDIASI KEPUASAN KONSUMEN PADA RUMAH MAKAN AMPALU RAYA PADANG - Kurnia, Iqbal; Besra, Eri (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: This research was conducted to determine the effect of productquality on consumer loyalty with mediating variables of customersatisfaction at the Ampalu Raya Padang Restaurant. To determine thesample in this study using simple random sampling with the criteria, (a)Answering domiciled in the city of Padang, (b) Knowing the Ampalu RayaRestaurant, (c) Medium or ever making a purchase more than twice. Thisstudy used a sample of 150 respondents obtained from the Hair method.This study uses quantitative methods and survey methods in collectingdata about attitudes, feelings, beliefs of past behavior and thoughts relatedto SEM-PLS 3 software. The results of this study reveal the quality of foodthat results in significant consumer loyalty in Ampalu Raya Restauant,product quality is important for consumers at Ampalu Raya Restaurant,customer satisfaction affects consumers significantly at Ampalu RayaRestaurant, customer satisfaction is related fully mediating product qualityto customers at Ampalu Raya Restauant. From the R2 value of customersatisfaction variables can be determined by the poduct quality variable of54.7 percent explained by other variables that are not examined, customerloyalty can be explained by product quality variable and customersatisfaction by 56.3 percent, the rest explained by variables othervariables not examinded.Key Words: Product Quality, Consumer Satisfaction, Consumer Loyalty